2009
DOI: 10.2298/aci0904189m
|View full text |Cite
|
Sign up to set email alerts
|

Conventional conformal radiotherapy vs intracavitary brachytherapy for the adjuvant postoperative treatment of cervical cancer: A comparative dosimetric study

Abstract: The referent volume received HDR-ICBT prescribed dose. The maximum ICBT percentage dose to the rectum and urinary bladder was 101% and 106% respectively. In all 3D-CRT plans almost 100% of planning target volume (PTV) was covered by 95% therapy isodose surface. From 12 - 13% of the rectum and 1-3% urinary bladder volume were covered by 100% isodose surface, with the highest maximum dose of 104% and 101%, respectively. Comparison of the PTV dose coverage and the maximum dose to the rectum and urinary bladder fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Six articles with very few patients were found that examined technical considerations and/or the feasibility of using EBRT as an alternative to BT. Three studies, using only one patient, investigated whether 3D-CRT and IMRT can achieve a brachy-like dose distribution for cervical cancer [68][69][70]. BT irradiation of the vaginal cuff of patients with endometrial cancer has also been simulated with advanced EBRT using two and four patients, respectively [71,72].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles with very few patients were found that examined technical considerations and/or the feasibility of using EBRT as an alternative to BT. Three studies, using only one patient, investigated whether 3D-CRT and IMRT can achieve a brachy-like dose distribution for cervical cancer [68][69][70]. BT irradiation of the vaginal cuff of patients with endometrial cancer has also been simulated with advanced EBRT using two and four patients, respectively [71,72].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies on prostate showed superiority of BT over EBRT for rectal and bladder dose. The skin was the only site where the VMAT plans were better for almost all parameters [ 62 , 63 , 65 , 66 , 70 ]. The thin, large-curvature target volume appears to be better irradiated by external beams.…”
Section: Discussionmentioning
confidence: 99%